INVESTIGATING STUDENTS’ ABILITY IN ANALYZING COMPLEX PROCEDURAL TEXT USING THE PROBING PROMPTING LEARNING MODEL - Feronika Patroli; Elvie A. Sepang; Thelma I. M. Wengkang (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
This study aims at exploring the ability of the 7th grade students in analyzing structure of complex procedure text using probing prompting learning model approach. This descriptive study was carried out at SMP Negeri 12 Manado located in Bunaken, Manado city. 20 7th grade students were the object of this study. The research was conducted from October to November in 2021 academic year. Data collection techniques involved observation and tests, while data analysis used the percentage formula. The results showed that students' ability to analyze the structure of complex procedural texts, especially on the topic